PENGARUH PENGETAHUAN KEUANGAN, KECERDASAN SPIRITUAL, PENGALAMAN KEUANGAN DAN LOCUS OF CONTROL TERHADAP PERILAKU PENGANGGARAN PENGUSAHA BATU BATA MERAH (DESA MENURAN KECAMATAN BAKI KABUPATEN SUKOHARJO) - Fakhrur Rozi Araniri; Adi Wiratno; Triani Arofah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This research aim to determine the effect of financial knowledge, spiritual intelegent, financial experince and locus of control on budgeting behavior in SMES brick stone maker in the Menuran village. In this study, using the population of SMES brick stone maker live at Menuran village, This research was conducted by distributing questionnaires to the respondents and using the purposive sampling method for sampling. The data obtained in this study were 90 respondents. The results of this study indicate that: (1) financial knowledge has no effect on budgeting behavior of brick stone maker on Menuran village, (2) spiritual intelegent has no effect on budgeting behavior of brick stone maker on Menuran village, (3) financial experience has no effect on budgeting behavior of brick stone maker on Menuran village, (4) locus of control has negatife effect to budgeting behaviour of brick stone maker on Menuran village.